On Some Properties of the Degenerate Exponential Function - Akugre, Thomas Awinba; Nantomah, Kwara; Iddrisu, Mohammed Muniru (Communications in Mathematics and Applications, 2024)
In this paper, we study some limit properties and inequalities involving the degenerate exponential function. Utilizing analytical methods, we also obtain some monotonic properties involving the function.